2020
DOI: 10.1111/evj.13374
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring equine ascarid and cyathostomin parasites: Evaluating health parameters under different treatment regimens

Abstract: Background Strongylid and ascarid parasites are omnipresent in equine stud farms, and ever‐increasing levels of anthelmintic resistance are challenging the industry with finding more sustainable and yet effective parasite control programs. Objectives To evaluate egg count levels, bodyweight and equine health under defined parasite control protocols in foals and mares at two Standardbred and two Thoroughbred stud farms. Study design Longitudinal randomised field trial. Methods A total of 93 foals were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Our results demonstrate a lack of seasonal differences in strongylid egg shedding among the mature horses. As outlined in the introduction, this is in stark contrast to both historical and more recent studies, which collectively demonstrated clear seasonal differences [ 11 , 18 – 22 ]. However, as mentioned previously, most of these previous studies were conducted in the UK, and since very few studies have been completed elsewhere, these patterns may differ substantially between regions and climates.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results demonstrate a lack of seasonal differences in strongylid egg shedding among the mature horses. As outlined in the introduction, this is in stark contrast to both historical and more recent studies, which collectively demonstrated clear seasonal differences [ 11 , 18 – 22 ]. However, as mentioned previously, most of these previous studies were conducted in the UK, and since very few studies have been completed elsewhere, these patterns may differ substantially between regions and climates.…”
Section: Discussionmentioning
confidence: 67%
“…In the past decade two British studies have been published, with one finding similar seasonal egg shedding patterns [ 19 ], while the other found no evidence of such seasonality among adult horses [ 20 ]. Recently, a Swedish 2.5-year study of free-ranging ponies found strongylid fecal egg counts (FECs) to peak in August/September [ 21 ], and a New Zealand study reported broodmares to exhibit lower strongylid FECs during winter months [ 22 ], both confirming Poynter’s observations from almost 70 years ago. One study performed in ponies in Louisiana, USA, reported significantly lower mean strongylid FECs during winter months, but these were data from ponies that were euthanized at different time points, and repeated measures were not done across seasons [ 23 ].…”
Section: Introductionmentioning
confidence: 76%
“…Poor body condition has been associated with Parascaris spp. infection in working equids (Getachew et al 2008 , 2010 ); however, foals under parasite management programs have not exhibited these signs in recent studies (Bellaw et al 2016 ; Nielsen et al 2021 ). Small intestine impaction is one of the largest concerns with this parasite, often requiring hospitalization and surgery, and can ultimately lead to death (Nielsen 2016 ; Southwood et al 1996 ; Cribb et al 2006 ; Tatz et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…48 In relation to prevalence and abundance, non-migratory small strongyles play the main role in horses in western Europe and most other regions of the world. 6,37,39 This group of parasites (also called cyathostomins and comprehending approximately 50 species) 26 is clinically relevant in case of larval cyathostominosis, induced by sudden eruption of encysted larvae into the intestinal lumen. This is a syndrome that occurs mostly seasonally in late winter or spring.…”
Section: Introductionmentioning
confidence: 99%